Early Judeo-Arabic Birth Narratives in the Polemical Story “Life of Jesus” (Toledot Yeshu) - Goldstein, Miriam (Harvard theological review, 2020)
This is a first-time presentation of the initial section of the Toledot Yeshu (TY) narrative describing the birth and early life of Jesus in Judeo-Arabic, a text with important implications for current research on TY. First, the origin of the birth narrative has been debated in recent scholarship on the Hebrew versions of TY. The existence of this lengthy Judeo-Arabic birth narrative, preserved in two manuscripts belonging to the Russian National Library, as well as the identification of other, earlier Judeo-Arabic manuscript fragments that include the TY birth narrative, demonstrates that the birth narrative formed part of TY significantly earlier than has been previously suggested. Second, the narrative preserved in the Russian manuscripts also demonstrates the relevance of the Judeo-Arabic versions of TY for the understanding of the development of this protean work. Examination of their textual tradition reveals interesting connections with particular Hebrew versions of TY from Europe and can shed light on the question of how the work moved between East and West. Finally, this Judeo-Arabic version of TY is significant in its demonstration of a clever adaptation to its linguistic and cultural surroundings. It incorporates a lengthy introduction—the only one currently known in all of the TY literature—which is a literary tour de force employing contemporaneous Arabic style together with a well-known rabbinic dictum, thereby situating Toledot Yeshu simultaneously in its Islamicate milieu and in Jewish textual and even ritual tradition. The discussion concludes with a transcription and translation of the birth narrative as preserved in these two Russian manuscripts.